The Effect of Position Promotion and Work Motivation on Employee Performance at PT. Honda Motor Medan - Amin Makhmud Zain NST; Dian Purnama Sari (PT Inovasi Pratama Internasional, 2022)
This study aims to determine whether there is an effect of promotion and work motivation on employee performance at PT. The Honda Motor Medan script and how much influence it has. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Partially, the variable of promotion (X1) has a significant influence on the performance of employees of PT. Honda Motor Medan script. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (1,686 > 1,678). While the work motivation variable (X2) has a significant influence on the performance of employees of PT. Honda Motor Medan script. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (4.801 > 1.678). Simultaneously, the variables of job promotion (X1) and work motivation (X2) have a significant influence on the performance of employees of PT. Honda Motor Medan script. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (79.051 > 3.25). Job promotion variables (X1) and work motivation (X2) were able to contribute influence on employee performance variables by 79.5% while the remaining 20.5% was influenced by other variables not examined in this study.